Pengaruh Penambahan MOL Bonggol Pisang Terhadap Kualitas Fisik dan Nutrisi Kulit Buah Kopi Sebagai Pakan Ternak: The Effect of Adding Banana Weevil Local Microorganism Activator (MOL) on The Physical and Nutritional Quality of Silage Coffee Husk as Animal Feed - Alwi, Annisa Lutfi; Vergianti, Chisdita; Kusumaningtyas, Rizky Nirmala; Nugroho, Setyo Andi; Respati, Adib Norma (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
Coffee husk waste can be used as animal feed, preventing environmental pollution, with 30.15% crude fiber and 6.77% protein. This study evaluates the impact of adding banana stem local microorganism activator (MOL) on coffee husk's physical quality and nutritional content for animal feed. This study used a Completely Randomized Design (CRD) with five banana stem MOL addition treatments. The treatments included: Ax (control, 0 ml), Bx (35 ml), Cx (40 ml), Dx (45 ml), and Ex (50 ml), each replicated three times. Parameters observed included physical quality (color, aroma, texture, and mold), crude fiber, crude protein, water content, and pH. Data were analyzed using the Kruskal-Wallis test for physical quality, and nutrient content data were analyzed using ANOVA, with further testing using the Tukey test at a 5% level for significant differences in treatment. The analysis showed that the Cx (40 ml) treatment had the best color with a value of 2.6, while the Ex (40 ml) treatment had a firm texture of 2.7. Both Dx (45 ml) and Ex (50 ml) treatments had a fresh sour aroma at a value of 2.73, and the Bx (35 ml) treatment showed no mold (2.53). The Cx (40 ml) treatment had the highest water content at 11.8%. All treatments had pH values around 4.2 to 4.5. The Ex (50 ml) treatment had the highest crude protein content at 1.51%. It can be concluded that adding banana stem MOL improves the physical quality and nutrient content of coffee skin silage when used at 50 ml.